Web-Based Geographic Information System Application for Mangrove Planting Planning in Pari City Village - Sri Wahyuni; Darmeli Nasution; Abdul Khaliq; Mhd Imam Maulana; Fikri Yolanda (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Kota Pari Village has a strategic coastal area but faces the challenge of degradation of mangrove ecosystems. Kota pari Village has the potential for mangrove forests that can be used as tourist attractions in coastal areas. This research aims to design a Geographic Information System (GIS) to support appropriate and sustainable mangrove planting planning. The research method uses a quantitative descriptive approach with data collection techniques through field observation, interviews, and spatial analysis. The research stages include collecting geographic data, mapping ecosystem conditions, analyzing land characteristics, and identifying potential zones for mangrove planting. The Geographic Information System is developed using Web-based software by considering parameters such as topography, soil type, salinity, and abrasion rate. The results of the study show that GIS has successfully identified 15 potential zones for mangrove planting with different levels of land suitability. This system is able to provide recommendations for planting locations, appropriate types of mangroves, and appropriate conservation strategies. This research makes a significant contribution to supporting mangrove ecosystem restoration efforts, sustainable development planning, and coastal area management in Kota Pari Village.